The Application of Ethno-ESD as a Strategy to Strengthen Sustainable Environmental Attitudes in Chemistry Education Students - Ariyatun Ariyatun; Sudarmin Sudarmin; Sri Wardani; Woro Sumarni; Maria Paristiowati (Journal of Educational Chemistry (JEC), 2025)
This study aims to analyze the effectiveness of the Engineering Design Project learning model based on Ethno-ESD in actualizing sustainable environmental literacy in Chemistry Education students. The method used was a quasi-experiment with the design of the One-Shot Case Study involving 46 fifth-semester students. The environmental literacy measurement instrument which includes the aspects of Sustainability Environmental, Sustainability Social, and Sustainability Economic was validated using Aiken's V analysis. After Ethno-ESD learning was applied, the test result data was analyzed through normality, homogeneity, and one-way ANOVA tests to determine the effectiveness of the treatment. The results show that all data are distributed normally and homogeneously, thus qualifying parametric analysis. The ANOVA test produced a value of F = 20.365 with a significance of 0.000, which indicates that the Ethno-ESD learning model has a significant effect on improving students' sustainable environmental literacy. This finding confirms that the integration of local wisdom with the principles of Education for Sustainable Development is able to improve students' knowledge, attitudes, and sustainable behaviors in the context of environmental chemistry learning. The Ethno-ESD model is recommended as an innovative approach to strengthen sustainable environmental literacy in higher education.